Role of Mitochondrial Respiratory Chain in Neurotoxic Action of Heavy Metals: Comparison of Cd2+, Hg2+ and Cu2+ - Elena A. Belyaeva (Cutting Edge Research in Biology Vol. 2, 2022)
The aim of the present work was to elucidate the role of mitochondrial electron transport chain (mtETC) in neurotoxicity of heavy metals, such as Cd2+, Hg2+ and Cu2+. In particular, the effects of these bivalent heavy metal ions on cell viability, intracellular reactive oxygen species generation, respiration and mitochondrial membrane potential of rat neuron-like PC12 cell line were studied in the absence and in the presence of various antioxidants and mitochondrial function modulators. As revealed, the metals under study caused, although in a different way, dose- and time-dependent changes of all aforementioned parameters. Noteworthy, beginning from 10 µM and already at short incubation time (3 h), Cd2+ significantly inhibited rates of maximally uncoupled cell respiration. In addition, almost complete suppression of cellular respiration was achieved after 3 h of incubation with 50 µM Hg2+ or 500 µM Cd2+, whereas even after 48 h of exposure to 500 µM Cu2+, only 50% suppression of respiration took place. It has been established that not only various antioxidants (N-acetylcysteine, butylhydroxytoluene, mannitol, vitamin E, tetramethylpiperidine-1-oxyl) and inhibitors of mitochondrial permeability transition (MPT) pores (cyclosporin A, bongkrekic acid, ruthenium red), but also such mtETC modulators as FCCP (a widely used artificial uncoupler) and stigmatellin (a complex III inhibitor), partially protect from cell damage produced by Cd2+. However, all used mtETC modulators did not protect against Hg2+- or Cu2+-induced cell injury. Importantly, stigmatellin was shown to be one of the strongest protectors against Cd2+-induced cell damage, producing a 15-20% increase in cell viability. Molecular mechanisms of the involvement of mtETC in heavy metal-induced mitochondrial membrane permeabilization and cell death are discussed. As a result, the relationship between mtETC and MPT pore has become clearer.